Optimal hybridization and amortized cost study of battery/supercapacitors system under pulsed loads. (May 2016) - Lahyani, Amine; Sari, Ali; Lahbib, Insaf; Venet, Pascal
Highlights: An experimental study of the degradation of a single VRLA battery and a battery combined with supercapacitors under pulsed load power is proposed. The battery performances were investigated for both aging policies. The battery capacity fade, the drop of its State of Health (SoH) and the increase of its internal resistance were recorded and studied. The paper also focuses on the determination of optimal filter constant that should be used for battery power filtering. The best amortized lifetime cost of the hybrid system is sought by taking into account the power dissipation and the cost of the battery and the supercapacitors. The cost effectiveness of the hybrid compared to the battery alone was highlighted. Abstract: Hybrid electrical energy storage systems (HESS) show promise for solving the problems and exploiting the benefits of heterogeneous electrical storage systems (ESS). This paper compares the performance of a lead-acid battery/supercapacitors hybrid to that of a battery alone under pulsed loads. Two types of aging protocols, using pulsed and smoothed power, were carried out on VRLA batteries at 40 °C. These protocols typically illustrate a single or hybrid battery's use for an Uninterruptible Power Supply. In HESS, the supercapacitors smooth the power demand applied to the battery, and, when idle, the battery charges the supercapacitors. The same amount of energy is extracted from the battery during both protocols. The experiment indicated that the battery alone performs 150 ten-minute-cycles before reaching the end of its life. In the hybridized battery, the power dissipated was reduced to 36% of that used by the battery alone, and the number of cycles increased by 70%. The use of a hybrid also reduced the battery's capacity fade by 60% and its increase of internal resistance by 83%. Finally, the amortized cost of the hybrid system was 17.6% less than that of the battery alone.